COGNITION AND MOOD/BEHAVIOR IN HOME CARE ELDERLY - Rivas, Claudia Maria Ferrony; Bolzan, Natalia Cassol; Santos, Naiana Oliveira dos; Bierhals, Carla Cristiane Becker Kottwitz; Gehlen, Maria Helena; Petter, Emilly Barcelos; Marques, Clandio Timm (Cogitare Enfermagem, 2023)
Objectives: to identify the sociodemographic characteristics; and to analyze the association of sociodemographic variables with functional systems related to cognition and mood/behavior of elderly people linked to Home Care. Method: cross-sectional, descriptive research, carried out with the participation of 108 elderly people linked to Home Care in the city of Santa Maria - RS - Brazil. We used a questionnaire of sociodemographic data and the Clinical and Functional Vulnerability Index IVCF-20. The association of the variables was analyzed using the chi-square test and independent samples test. Results: predominance of elderly females; mean age 78.7 ± 9.3 years; and low education and family income between 1 and 2 minimum wages. The most frequent morbidity was systemic arterial hypertension. No associations were found between the sociodemographic variables and the functional systems regarding cognition and mood/behavior. Conclusion: the importance of planning and interventions in the home environment is highlighted.